Relationship Between Growth Trajectories and Functional Traits for Woody Trees in a Secondary Tropical Forest - Scalon, Marina Corrêa; Bohn, Amabily; Coelho, Geraldo Ceni; Meister, Luana; Alves, Rangel de Freitas; Secco, Rubia Tatiana; Zwiener, Victor P.; Marcilio-Silva, Vinicius; Trindade, Weverton C. F.; Marques, Marcia C. M. (Frontiers in Forests and Global Change, 2022)
Absolute growth rates change with tree size and age, shifting throughout species ontogeny. The study on interspecific variation in plant traits has generated important insights into the life-history strategies and their consequences for ecosystem functioning. However, it remains unknown to what extent - and even if - species' functional traits are related to the variation in their growth trajectories. We set out to model growth trajectories of 45 woody species from the Brazilian Atlantic Forest in a secondary subtropical forest under regeneration, aiming to understand if species can be grouped by their growth patterns throughout ontogeny and if these groups could be classified in distinct ecological strategies based on key plant traits. We used a maximum likelihood estimation approach to predict growth trajectories using three ecologically relevant parameters (maximum growth rate [Gmax], diameter at maximum growth rate [Dopt], and the ontogenetic variability in growth rate [K]) followed by multivariate analyses to detect associations among phylogenetic relationships, plant traits, and growth parameters and classify species into growth pattern groups. Across species, growth trajectory parameters varied widely. The cluster analysis identified three distinct groups based on growth trajectories parameters, which were not functionally or ecologically well defined. Our findings supports the idea that traits describing plant size and tree shape, such as maximum height, canopy volume and height to diameter ratio, were generally the best predictors of species growth parameters throughout ontogeny, even though traits representing resource-use and reproductive strategies also played a significant role. Growth-trait framework can be understood as a continuum of multi-trait combinations where, at one end of the gradient, we find trees with higher growth rate and larger diameters supporting a voluminous canopy combined with lower investment in leaf tissue and smaller diaspore; at the other end, taller trees supporting a smaller canopy with higher investment in leaf tissue and longer diaspore. Ultimately, we have shown that tree architecture, leaf and reproductive traits significantly influence growth trajectory along tree ontogeny, which may be the reason why objectively grouping species based on growth-trajectories parameters is ineffective, at least in highly diverse secondary subtropical forests undergoing regeneration.